2022
DOI: 10.1136/jim-2021-002134
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of IL-37 and Correlation with Inflammatory Cytokines and Clinical Outcomes in Patients with Coronary Artery Disease

Abstract: Coronary artery disease (CAD) due to atherosclerosis is one of the important reasons for death worldwide. Recent evidence has suggested the essential role of inflammation in the progression of atherosclerosis. Interleukin (IL)-37 is a critical anti-inflammatory member of the IL-1 family which regulates the inflammatory processes. The aim of this study was to compare the serum levels of IL-37 in patients with CAD compared with the control group and its correlation with oxidative stress, cholesterol homeostasis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…This imbalance might exacerbate vascular extracellular matrix remodeling and arterial stiffening [ 136 ]. For example, treatment with IL-37, a critical anti-inflammatory interleukin in humans [ 141 ], improves vascular endothelial function, endurance exercise capacity, and whole-body glucose metabolism in old mice [ 142 ].…”
Section: Aging-related Changes In Skeletal Muscle and Cardiovascular ...mentioning
confidence: 99%
“…This imbalance might exacerbate vascular extracellular matrix remodeling and arterial stiffening [ 136 ]. For example, treatment with IL-37, a critical anti-inflammatory interleukin in humans [ 141 ], improves vascular endothelial function, endurance exercise capacity, and whole-body glucose metabolism in old mice [ 142 ].…”
Section: Aging-related Changes In Skeletal Muscle and Cardiovascular ...mentioning
confidence: 99%
“…Although numerous risk factors for CAD have been identified and studied, including circulating miRNAs, blood lipids, cholesterol, glucose, and inflammatory factors [ [17] , [18] , [19] , [20] ], utilizing these factors to predict CAD risk is not yet common. This is due to the large variability of some of these factors in different individuals, particularly inflammatory factors, which have been shown to be associated with CAD risk but are also sensitive to environmental factors such as diet and infection.…”
Section: Introductionmentioning
confidence: 99%
“…IL-37 is a newly identified anti-inflammatory factor; it was found that IL-37 is significantly elevated in monocytes as well as in peripheral blood in patients with coronary artery disease and acute myocardial infarction (8,9). Moreover, IL-37 levels have also been shown to be strongly associated with the long-term prognosis of patients with acute myocardial infarction and acute stroke (10)(11)(12)(13). Furthermore, it was also reported that overexpression of IL-37 significantly increases plaque instability in ApoE -/mice (14).…”
Section: Introductionmentioning
confidence: 99%